PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KEPERCAYAAN MASYARAKAT DALAM PENGELOLAAN DANA DESA DI DESA SEGARAU PARIT KECAMATAN TEBAS KABUPATEN SAMBAS - Sabirin, Sabirin; Priyoga; Verdianti (Universitas Sarjanawiyata Tamansiswa, 2025)
Village funds are funds used to finance government administration, development implementation, community development, and community empowerment. The provision of large village funds makes it vulnerable to fraud in the management of village funds. therefore the need to apply accountability and transparency in order to increase public trust in the village government in the management of village funds. The purpose of this study was to determine The effect of accountability and transparency on public trust in the management of village funds. The research method used is quantitative method, data collection techniques in the form of questionnaires, with the stages of testing research instruments, classical assumption tests, multiple regression analysis, hypothesis testing, and the coefficient of determination. Multiple regression, hypothesis testing, and coefficient of determination. The results showed: Accountability affects public trust in the management of village funds. Transparency affects public trust in the management of village funds. Accountability and transparency affect public trust in the management of village funds.